Understanding language teaching : from method to post-method - Kumaravadivelu, B., 1948- (ESL and applied linguistics professional series, 2006)
"This book traces the historical development of major language teaching methods in terms of theoretical principles and classroom procedures, and provides a critical evaluation of each. Drawing from seminal, foundational texts and from critical commentaries made by various scholars, Kumaravadivelu examines the profession's current transition from method to postmethod and, in the process, elucidates the relationship between theory, research, and practice. The chief objective is to help readers see the pattern that connects language, learning, teaching methods, and postmethod perspectives." "Understanding Language Teaching: From Method to Postmethod is intended for an international audience of teacher educators, practicing teachers and graduate students, researchers, curriculum planners, and materials designers in the field of second and foreign language teaching."--BOOK JACKET.